2012
DOI: 10.1039/c2dt31110k
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and ATP binding by mononuclear Zn(ii) complexes with non-symmetric ditopic polyamine ligands

Abstract: Binding of Zn(II) by the ditopic ligands L1py, L2py and L1para, composed of a cyclam unit linked to the linear polyamines 1,4,8,11-tetraazaundecane (L1py and L2para) and 1,4,7-triazaheptane (L2py) via a 2,6-dimethylpyridinyl (L1py and L2py) or a 1,4-dimethylbenzyl spacer (L2para), has been analyzed by means of potentiometric and (1)H and (13)C NMR measurements. All ligands form stable mononuclear Zn(II) complexes in a wide pH range, featuring the metal ion bound to the macrocyclic unit. The open-chain polyamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Because of the similar atomic number of N and O, EXAFS cannot distinguish between these two elements as backscattering atoms. However, according to previous structural studies on metal/glyphosate complexation ,, and Zn/organic ligand complexation, we presumed the presence of direct bonding between Zn and N in the first shell. For the second shell, we can satisfactorily fit it with 1 C atom at 2.90 Å, suggesting that Zn complexed with the carboxyl group of glyphosate.…”
Section: Resultsmentioning
confidence: 94%
“…Because of the similar atomic number of N and O, EXAFS cannot distinguish between these two elements as backscattering atoms. However, according to previous structural studies on metal/glyphosate complexation ,, and Zn/organic ligand complexation, we presumed the presence of direct bonding between Zn and N in the first shell. For the second shell, we can satisfactorily fit it with 1 C atom at 2.90 Å, suggesting that Zn complexed with the carboxyl group of glyphosate.…”
Section: Resultsmentioning
confidence: 94%
“…There are four sets of scaffolds: mono-DPA scaffolds with one or two appended 2-amido substituents (compounds 6 and 10 ) and bis-DPA scaffolds with two or four appended 2-amido substituents (compounds 7 and 11 ). The focus on 2-amido substituents was intentional because literature precedence suggested that the NH residues were likely to form attractive hydrogen bonds to the proximal oxyanion residues within the headgroup of a bound PS (Scheme ). …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 1, the primary coordination bonding with the two zinc cations is strengthened by additional secondary noncovalent interactions with the PS headgroup such as electrostatic attraction, hydrogen bonding, and hydrophobic insertion into the membrane. 33,34 The molecular design concept of modified scaffolds has been used before to enhance binding affinity of Zn-BDPA structures to small, water-soluble phosphorylated target molecules such as inorganic phosphate, 3538 nucleoside polyphosphates, 39 and phosphorylated peptides. 4042 However, there is no reported attempt to improve Zn-BDPA recognition of PS buried in a bilayer membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 , 24 , 25 , 26 , 27 ] The formation of macrochelates was clearly defined for adenine nucleotides, thanks to the coordination of both the phosphate chains and the nitrogen N-7 of the purine residue. [ 28 , 29 ] Since then, different types of molecular receptors have been used for the recognition of phosphorylated anions in aqueous media [ 1 ]: (1) Linear or macrocyclic positively charged receptors, generally polyammonium systems [ 30 , 31 , 32 , 33 ] or receptors containing guanidinium or imidazolium groups [ 34 , 35 ]; (2) Metal complexes, generally coordinatively unsaturated Cu 2+ or Zn 2+ complexes, with acyclic (i.e., dipicolyl or terpyridyl derivatives [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ] or Schiff base ligands [ 43 ]) or macrocyclic ligands [ 44 , 45 , 46 ]; (3) Ditopic receptors that combine a metal coordinating unit and hydrogen-bond donors to reinforce anion binding [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%